The spray-paint mystery - Medearis, Angela Shelf, 1956-; Papp, Robert (New York : Scholastic, 1996)
Someone's been painting graffiti on the walls. It's up to Cameron to find out who and prove that he can be a great detective just like his dad. With help from his best friend, Tarann, it's up to him to solve this paint puzzle!
"A Little Apple paperback."
b
b
Keywords: Graffiti -- Juvenile fiction; Mystery fiction; Children's stories